2019
DOI: 10.1111/tbed.13382
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of visits of wild fauna to a commercial free‐range layer farm in the Netherlands located in an avian influenza hot‐spot area assessed by video‐camera monitoring

Abstract: Free‐range poultry farms have a high risk of introduction of avian influenza viruses (AIV), and it is presumed that wild (water) birds are the source of introduction. There is very scarce quantitative data on wild fauna visiting free‐range poultry farms. We quantified visits of wild fauna to a free‐range area of a layer farm, situated in an AIV hot‐spot area, assessed by video‐camera monitoring. A total of 5,016 hr (209 days) of video recordings, covering all 12 months of a year, were analysed. A total of 16 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(76 citation statements)
references
References 56 publications
2
72
1
1
Order By: Relevance
“…As such, IAV infections and exposures have been commonly detected in a broad diversity of hawks, eagles, owls, and vultures, e.g., [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Farms are frequently used by a number of species in these groups for foraging opportunities, and these birds are regularly observed at poultry facilities, including foraging on carcasses ([ 21 , 22 ], personal observations).…”
Section: Scavengers and Raptors: Orders Accipitriformes Cathartifmentioning
confidence: 99%
See 3 more Smart Citations
“…As such, IAV infections and exposures have been commonly detected in a broad diversity of hawks, eagles, owls, and vultures, e.g., [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Farms are frequently used by a number of species in these groups for foraging opportunities, and these birds are regularly observed at poultry facilities, including foraging on carcasses ([ 21 , 22 ], personal observations).…”
Section: Scavengers and Raptors: Orders Accipitriformes Cathartifmentioning
confidence: 99%
“…However, other virus subtypes are sometimes isolated from gulls, and many gull species exhibit synanthropic behavior, so these species might play a role in the spillover of IAVs of consequence to poultry. Black-headed gulls ( Chroicocephalus ridibundus ) were commonly observed on a poultry farm in Switzerland [ 21 ], and black-headed gulls and lesser black backed gulls ( Larus fuscus ) were frequent visitors to poultry farms in the Netherlands [ 22 ]. Additionally, an epidemiological assessment of risk factors associated with HP IAV outbreaks on ostrich farms in South Africa showed that the presence of gulls was associated with an increased likelihood of an outbreak [ 28 ].…”
Section: Gulls: Order Charadriiformes Family Laridaementioning
confidence: 99%
See 2 more Smart Citations
“…This water-rich area provides a good habitat for wild (water) birds, which live in large quantities near the farm. Elbers and Gonzales (42) monitored the free-range area of this particularly farm with video-cameras for 1 year and reported various visits of wild birds to the freerange area (42). No direct contact between hens and wild birds was observed, and it is hypothesized that wild birds infected with AIV probably contaminate the environment-soil and water present in the free-range area-with AIV.…”
Section: Outbreak Descriptionmentioning
confidence: 99%